2017
DOI: 10.1002/gj.3097
|View full text |Cite
|
Sign up to set email alerts
|

Jurassic sedimentary provenances of the Hongshan and Huobuxun sags in the eastern segment of the northern Qaidam Basin: Basin–Mountain coupling

Abstract: The Hongshan and Huobuxun sags are located in the eastern segment of the northern Qaidam Basin, and the provenances of Jurassic deposits in the two sags are unclear. Based on the tectonic setting of the northern Qaidam Basin before the Jurassic, this paper discusses provenances of the two sags by field geological survey, analysis of detritus, and heavy minerals of the Jurassic strata. The Jurassic sedimentation in the Hongshan Sag mainly came from the Zongwulong Orogen and the Oulongbuluke and Kuerleike mounta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Provenance interpretations of Jurassic sediments can provide data for surrounding mountains tectonic evolution of Qaidam Basin, thus enhancing the understanding of the uplift events in north‐eastern Tibetan Plateau. In recent years, research based on petrography (Feng et al, ; Tang et al, ; Wu et al, ), geochemistry (Cao et al, ; Jian et al, ), and heavy mineral (Shu et al, ) were carried out, but the detailed and systematic provenance studies of the sediments are relatively scarce. Dameigou profile sandstone detrital zircon geochronological studies were reported both by Yu et al () and Qian et al (), but the results indicate different Jurassic primary source areas.…”
Section: Introductionmentioning
confidence: 99%
“…Provenance interpretations of Jurassic sediments can provide data for surrounding mountains tectonic evolution of Qaidam Basin, thus enhancing the understanding of the uplift events in north‐eastern Tibetan Plateau. In recent years, research based on petrography (Feng et al, ; Tang et al, ; Wu et al, ), geochemistry (Cao et al, ; Jian et al, ), and heavy mineral (Shu et al, ) were carried out, but the detailed and systematic provenance studies of the sediments are relatively scarce. Dameigou profile sandstone detrital zircon geochronological studies were reported both by Yu et al () and Qian et al (), but the results indicate different Jurassic primary source areas.…”
Section: Introductionmentioning
confidence: 99%
“…In the paper by Peng et al (), the focus of the study was on Early Paleozoic arc magmatism and metamorphism in the northern Qilian Block. The final three papers in this region by H. Feng et al (); Shu et al (); and Z. Tang et al () all concentrate on aspects of Jurassic basin sedimentation characteristics, and provenance in the northern Qaidam Block.…”
Section: Volume 1 Structure and Main Themesmentioning
confidence: 99%